2010
DOI: 10.1002/bmc.1502
|View full text |Cite
|
Sign up to set email alerts
|

Indirect reversed‐phase high‐performance liquid chromatographic and direct thin‐layer chromatographic enantioresolution of (R,S)‐Cinacalcet

Abstract: Enantioresolution of the calcimimetic drug (R,S)-Cinacalcet was achieved using both indirect and direct approaches. Six chiral variants of Marfey's reagent having L-Ala-NH(2), L-Phe-NH(2), L-Val-NH(2), L-Leu-NH(2), L-Met-NH(2) and D-Phg-NH(2) as chiral auxiliaries were used as derivatizing reagents under microwave irradiation. Derivatization conditions were optimized. Reversed-phase high-performance liquid chromatography was successful using binary mixtures of aqueous trifluoroacetic acid and acetonitrile for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…10) introduced by Bhushan and Tanwar showed successful separation of diastereomers of dl-PenA on RP-HPLC with the advantage of one step room temperature derivatization and low detection limits (0.5-2.5 pmol range) [178]. (S)-Naproxen-benzotriazole as a new CDR was introduced by Bhushan et al to prepare diastereomers of PenA, Cys and homocysteine under microwave irradiation [179], and 18 proteinogenic amino acids by microwave irradiation and vortexing [180] followed by their separation on RP-HPLC with UV detection at 231 nm. In conclusion, they highlighted that the large, highly conjugated naphthyl ring of CDR attached to the chiral center offers high UV absorbance and gives detection at very low concentration (LOD 0.1-1.2 pmol range), and the hydrophobic property of the naphthyl ring facilitates enantioresolution.…”
Section: Other Cdrsmentioning
confidence: 98%
“…10) introduced by Bhushan and Tanwar showed successful separation of diastereomers of dl-PenA on RP-HPLC with the advantage of one step room temperature derivatization and low detection limits (0.5-2.5 pmol range) [178]. (S)-Naproxen-benzotriazole as a new CDR was introduced by Bhushan et al to prepare diastereomers of PenA, Cys and homocysteine under microwave irradiation [179], and 18 proteinogenic amino acids by microwave irradiation and vortexing [180] followed by their separation on RP-HPLC with UV detection at 231 nm. In conclusion, they highlighted that the large, highly conjugated naphthyl ring of CDR attached to the chiral center offers high UV absorbance and gives detection at very low concentration (LOD 0.1-1.2 pmol range), and the hydrophobic property of the naphthyl ring facilitates enantioresolution.…”
Section: Other Cdrsmentioning
confidence: 98%
“…[12] This high enables the determination of trace amounts of cinacalcet hydrochloride in either its bulk powder or tablets. …”
Section: Range Linearity and Sensitivitymentioning
confidence: 99%
“…These methods include spectrophotometric, [10] fluorimetric, [11] and liquid chromatographic techniques. [12][13][14][15] No stability-indicating assay was described for cinacalcet hydrochloride.…”
Section: Introductionmentioning
confidence: 99%
“…Ravinder et al (2009) reported enantiomeric separation of CIN on Chiralpak-IA column in normal phase mode. Bhushan and Dubey (2011) developed a derivatization method with chiral reagents for separation of CIN enantiomers. However, these methods are not applicable to clinical pharmacokinetics and, in the literature, so far no method has been reported in polar ionic mode for chiral separation of CIN enantiomers on columns packed with vancomycin as a chiral stationary phase.…”
Section: Introductionmentioning
confidence: 99%